Vitamin D3 levels in allergic rhinitis: a case control study from South Karnataka - Bhat, Vinay S.; A., Anupama (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Allergic rhinitis (AR) is a common disorder seen in routine otolaryngology practice. There has been an increased interest in researchers worldwide regarding role of vitamin D3 in pathogenesis of allergy. This study intends to compare levels of vitamin D3 in patients with clinically diagnosed allergic rhinitis and subjects without allergic rhinitis. This study was conducted in rural South Karnataka where incidence of allergic rhinitis is on the rise. Main objective of this study was to assess vitamin D3 levels in patients with clinically diagnosed AR and compare it with vitamin D3 levels in control group where normal subjects were included. Methods: Total of 100 patients were included in this study. Case group comprised of 50 patients clinically diagnosed as AR and control group comprised 50 subjects without any symptoms of AR. All the patients underwent serum vitamin D3 estimation. Other parameters such as age, gender, occupation (outdoor vs indoor) and region of residence (urban vs rural) were also compared between the groups. Results: This study did not find significant difference between two groups when all the parameters compared. Significant number of study subjects both in case and control group were found to be either deficient or inadequate in vitamin D3 levels. Conclusions: we did not find significant difference in vitamin D3 levels between cases and controls. Further studies with bigger sample size and robust study design may throw more light on association of vitamin D3 with AR.